On the seasonal and sub-seasonal factors influencing East China tropical cyclone landfall - Sparks,N; Toumi,R (Atmospheric Science Letters, 2021)
To date it has proved difficult to make seasonal forecasts of tropical cyclones, particularly for landfall and in East China specifically. This study examines sources of predictability for the number of landfalling typhoons in East China on seasonal (June–October) and subseasonal time scales. East China landfall count is shown to be independent of basinscale properties of TC tracks, such the genesis location, duration, basin track direction and length, and basin total count. Largescale environmental climate indices which are potential basin scale drivers are also shown to be largely uncorrelated with landfall prior to and throughout the season. The most important factor is the steering in the final stages to landfall. The seasonal landfall is strongly anticorrelated with the more local zonal midtropospheric wind field over the East China sea (r = −.61, p < .001). It is proposed that geopotential height anomalies over Korea/Japan cause anomalous easterly winds in the East China Sea and enhance landfall rates by steering typhoons onto the coast. Early, peak, and late subseasonal landfall counts are shown to be independent of each other yet share this predictor. This local feature may be dynamically predictable allowing a potential hybrid dynamicalstatistical seasonal forecast of landfall.